2022
DOI: 10.1101/2022.01.10.22269007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of Full Vaccination and Post-Covid Olfactory Dysfunction in Recovered Covid-19 Patient. A Retrospective Longitudinal Study With Propensity Matching

Abstract: Background Symptoms after Coronavirus Disease (COVID-19) infection affect the quality of life of its survivor especially to the special senses including olfactory function. It is important to prevent the disability at an earlier stage. Vaccination as key prevention has been proven to be effective in reducing symptomatic disease and severity. However, the effects of vaccination on post COVID symptoms have not been evaluated. This study aimed to evaluate the possible protection of full vaccination and the occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
7
0
2
Order By: Relevance
“…UK Health Security Agency [18] published a rapid evidence briefing on the effectiveness of vaccination against long-COVID. In their analysis, six of the 8 studies suggested that vaccinated cases were less likely to develop symptoms of long-COVID in the short term (within 4 weeks after infection), medium term (12 to 20 weeks after infection) and long term (6 months after infection) [4][5][6][7][8]. Antonelli et al [28] found that fully vaccinated patients were almost half as likely to have symptoms lasting ≥ 28 days than unvaccinated patient (OR = 0.51, 95% CI: 0.32 to 0.82, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UK Health Security Agency [18] published a rapid evidence briefing on the effectiveness of vaccination against long-COVID. In their analysis, six of the 8 studies suggested that vaccinated cases were less likely to develop symptoms of long-COVID in the short term (within 4 weeks after infection), medium term (12 to 20 weeks after infection) and long term (6 months after infection) [4][5][6][7][8]. Antonelli et al [28] found that fully vaccinated patients were almost half as likely to have symptoms lasting ≥ 28 days than unvaccinated patient (OR = 0.51, 95% CI: 0.32 to 0.82, p = 0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Al–Aly et al [4] reported in their retrospective cohort study that vaccinated cases were less likely to have at least one post-acute sequelae of COVID-19 at 6 months compared with the unvaccinated cases (HR = 0.87, 95% CI: 0.83 to 0.92). A retrospective cohort study by Herman et al [5] found that fully vaccinated patients were less likely to develop of olfactory dysfunction after infection than unvaccinated patients (OR = 0.31, 95% CI: 0.10 to 0.94), but there was little evidence for an association between full vaccination and olfactory dysfunction at 4 weeks after end of infection (P = 0.59). An Israeli study by Koudi et al [6] found that those with 2 or 3 doses of vaccine were 54% to 83% less likely to report 7 of the 10 most commonly reported symptoms than the unvaccinated.…”
Section: Discussionmentioning
confidence: 99%
“…Tab. 1), wovon 7 zeigen, dass die COVID-19-Impfung mit einem reduzierten Long-COVID-Risiko assoziiert ist, wobei dies in 6 Fällen [19][20][21][22][23][24][25] für die vollständige Impfung und in einem Fall für die Einfachimpfung zutraf [25]. Zwei dieser Studien unterschieden nicht, ob die Impfung vor oder nach Infektion stattgefunden hat [24,25].…”
Section: Covid-19-impfung Zur Prävention Von Long-covidunclassified
“…Eine indonesische Studie beschäftigte sich mit Geruchsstörungen nach SARS-CoV-2-Infektion; diese traten 2 Wochen nach Freitesten bei vollständig Geimpften in geringerem Ausmaß auf als in der Kontrollgruppe ("adjusted odds ratio" [aOR] 0,31, 95 %-KI 0,102-0,941), waren allerdings wieder häufiger, je länger der Infektionszeitpunkt von der Impfung entfernt war [21].…”
Section: Impfung Vor Sars-cov-2-infektionunclassified
“…However, there is limited study on how the different variants affect the occurrence of residual symptoms. For example, a longitudinal study in Indonesia addressed persistent symptoms, including fatigue, chronic cough, and chronic headache within 90 days [8], and the impact of vaccination against specific symptoms, such as olfactory dysfunction [9]. However, these studies did not cover the current period where the Omicron is the most prevalent strain.…”
Section: Introductionmentioning
confidence: 99%